Optimizing Structural Connections: Finite Element Analysis of Extended End Plates and Bolt Dynamics - Fatimah De'nan; Nor Salwani Hashim; Nurul Ain Abd Wahab (Electronic Journal of Structural Engineering)
This study analyzed the connection using finite element (FE) simulations and nonlinear analysis to determine its moment resistance and mode of failure. In this work, FEA (finite element analysis) is employed to analyze the triangular web profiled (TRIWP) steel section as a beam element and extended end plate connection. The connection model has been developed with different thicknesses of extended end plate, beam flange, and beam web, and these parameters were analyzed to determine the relationship between all three cases with the failure connections and moment-rotation curve. Furthermore, the results obtained from the analysis of using extended end plate connections have been compared with previous studies where flush end plate connections are used to compare the behavior of the two end plates' connections. Twelve LUSAS analysis models were used, varying parameters such as the thickness of the flange beam, web beam, and end plate. Results indicated that an increased end plate thickness led to a higher moment resistance. A comparison of the moment resistance between the extended end plate and flush end plate connections, from a previous study, showed a difference of 48%. This finding is attributed to the extended end plate's ability to sustain a higher moment compared to the flush end plate. Therefore, the extended end plate connection is stronger than the flush end plate connection. Failure modes showed that buckling occurred at the top flange, which was similar for both types of connections. The use of a triangular shape is used to create contrast as this is prominent from the other shapes used commonly in web design.